Complication of Anterior Iliac Bone Graft Harvesting in 372 Adult Patients from May 2006 to May 2011 and a Literature Review. Issue 4 (December 2013) - Almaiman, Manar; Al-Bargi, Hamed H.; Manson, Paul
Autogenous bone graft from the iliac is considered the gold standard graft material in maxillofacial surgery. The common and the rare complications associated with harvesting bone from anterior iliac crest were reviewed; we recommend a safe technique to avoid these complications. A retrospective analysis of 372 adult patients who had undergone anterior iliac bone graft harvesting from May 2006 to May 2011. The patients age range from 21 to 63 years. Out of the 372 patients, 200 were male with age range from 21 to 63 years and 172 were female with age range from 22 to 59 years. Two major complications (fracture and seroma) occurred, a fracture of the anterior superior iliac spine was observed in two patients (0.538%); one male and one female. One female patient (0.269%) developed seroma. One minor complication occurred in three patients (0.806%); one female and two females who suffered from temporary sensory disturbance. All patients (100%) suffered pain maximum for the first 15 days postoperative. In our study; the morbidity after anterior iliac bone graft harvesting was found to be low due to the technique, utilizing the proper instruments, gentle and minimal mobilization of the graft.